Clinical results of fibroblast activation protein (FAP) specific PET and implications for radiotherapy planning: systematic review - Windisch, Paul; Zwahlen, Daniel R.; Körber, Stefan A.; Giesel, Frederik L.; Debus, Jürgen; Haberkorn, Uwe; Adeberg, Sebastian (Cancers, 2020)
Small molecules targeting fibroblast activation protein (FAP) have emerged as a new group of tracers for positron emission tomography (PET) in 2018. The purpose of this systematic review is therefore to summarize the evidence that has been gathered to date in patients and to discuss its possible implications for radiotherapy planning. The MEDLINE database was searched for the use of FAP-specific PET in cancer patients and the records were screened according to PRISMA guidelines. Nineteen studies were included. While dedicated analyses of FAP-specific PET for radiotherapy planning were available for glioblastoma, head and neck cancers, lung cancer, and tumors of the lower gastrointestinal tract, there is still very limited data for several epidemiologically significant cancers. In conclusion, FAP-specific PET represents a promising imaging modality for radiotherapy planning that warrants further research.